Malignant fibrous histiocytoma of the gingiva. (19th December 2012) - Vijayalakshmi, D; Fathima, Shabana; Ramakrishnan, K; Devi, M
Abstract : Malignant fibrous histiocytoma (MFH) is widely regarded as the commonest soft tissue sarcoma of adulthood which tends to occur in the deep soft tissues of the extremities and the retroperitoneum. Uncertain histogenesis and numerous subtypes make MFH a rather controversial entity. These tumours are relatively rare in the head and neck region accounting for only 1–3% of all cases of MFH. MFH exhibits a heterogenous histology of spindle cells in a characteristic storiform pattern with pleomorphic tumour cells and giant cells. A case is reported of an MFH of the gingiva in a 60-year-old woman who presented with a painful swelling originating from the left maxillary gingiva. The clinical, histopathological and immunohistochemical findings are discussed.